Gender inequality in COVID-19 times: Evidence from UK Prolific participants - Sonia Oreffice; Climent Quintana-Domeque (Global Labor Organization (GLO), 2020)
We investigate gender differences across multiple dimensions after three months of the first UK lockdown of March 2020, using an online sample of approximately 1,500 Prolific respondents residents in the UK. We find that women's mental health was worse than men's along the four metrics we collected data on, that women were more concerned about getting and spreading the virus, and that women perceived the virus as more prevalent and lethal than men did. Women were also more likely to expect a new lockdown or virus outbreak by the end of 2020, and were more pessimistic about the contemporaneous and future state of the UK economy, as measured by their forecasted contemporaneous and future unemployment rates. We also show that, between earlier in 2020 before the outbreak of the Coronavirus pandemic and June 2020, women had increased childcare and housework more than men. Neither the gender gaps in COVID-19-related health and economic concerns nor the gender gaps in the increase in hours of childcare and housework can be accounted for by a rich set of control variables. Instead, we find that the gender gap in mental health can be partially accounted for by the difference in COVID-19-related health concerns between men and women.
Keywords: H1; J1; J16; 330; Coronavirus; sex; inequity; wellbeing; mental health; anxiety; employment; concerns; perceptions; donations; time allocation; childcare; housework